Mild and Selective Organocatalytic Iodination of Activated Aromatic Compounds - Jakab, Gergely; Hosseini, Abolfazl; Hausmann, Heike; Schreiner, Peter R. (Synthesis, 2013)
We describe an organocatalytic iodination of activated aromatic compounds using 1,3-diiodo-5,5-dimethylhydantoin (DIH) as the iodine source with thiourea catalysts in acetonitrile. The protocol is applicable to a number of aromatic substrates with significantly different steric and electronic properties. The iodination is generally highly regioselective and provides high yields of isolated products. NMR kinetic investigations conducted in THF-d8 indicate the role of sulfur in the thiourea motif as a nucleophile that is assisted by H-bonding in the key steps of the reaction.
Keywords: catalysis; electrophilic aromatic substitution; halogenation; iodine; thiourea